Bryophila perloides Guenée, 1852 (Lepidoptera: Noctuidae: Bryophilinae), an overlooked member of the European Noctuidae fauna, with upgrading of Bryopsis Boursin, 1970 to generic level (Taxonomic studies on the western Palaearctic Bryophilinae, No. 1) - Vargas-Rodríguez, Suraya M.; Fibiger, Michael; Honey, Martin R.; Ronkay, Gábor; Yela, José Luis; Zilli, Alberto; Ronkay, László (Zootaxa, 2020)
The generic level segregation of the formerly unified taxa Nyctobrya Boursin, 1957 and Bryopsis Boursin, 1970 is discussed; the second one is reinstated as a genus, on the basis of apomorphic features in the male genitalia (Bryopsis stat. rev.). The large genus Bryophila Treitschke, 1825 is briefly characterized, in order to assess the specific identity of the formerly misinterpreted Bryophila perloides Guenée, 1852, the only European member of its species-group. So far as is known, B. perloides (stat. rev.) inhabits the southernmost, pericoastal area of Andalusia (Spain), and is known to date from five specimens. It is, thus, to be included in the Iberian and European checklists of Noctuidae. All other described species of the perloides species-group are North African. They are reviewed and their types checked; the adults, as well as their genitalia, are illustrated. Genitalia of all holotypes/syntypes are studied. Also, lectotypes are designated for B. perloides, B. squamosa Schwingenschuss, 1936 and B. barbaria Schawerda, 1934.